Rojava e democracia radical: entre o estado de exceção e o poder desinstituinte - Ana Clara Abrantes Simões (2021)
Rojava is in northern Syria, a region mostly inhabited by Kurdish ethnic groups. In 2011, during the Syrian War, residents of the region began organizing into communes and assemblies as a way to resist the oppressive Bashar al-Assad regime in Syria and to think of new and more democratic experiences. From this initiative, multiethnic and feminist and organizations have sprung up throughout the region. The movement expanded to other cities and regions. In 2012, Rojava declared itself an autonomous region. Despite the constant attacks suffered by different agents and groups, as the Turkish State and ISIS, Rojava daily builds des-instituting experiences, for example, the redistribution of defense mechanisms (popular self-protection forces) and the feminists communes (connecting with the impressive historical resistance of Kurdish women and the teaching of Jinealogy). Given the openness and complexity of this movement, this dissertation intends to conduct the analysis of Rojava as a radical democratic experience. Radical democracy, based on Andityas Matos’ theory, is to think of a new political experience, in which the des-instituting power and the constituent power are constantly manifesting and relating, denying the constituted power founded on the state of permanent economic exception. Therefore, to conceive and build radically democratic experience, based on a radical and counter-State philosophy is to think of an a-nomic and an-archic community based on the absence of government and separating spaces and on the rupture with hierarchical, representative and patriarchal structures. Radical democracy, thus, points to a criticism and general reaction to the current exceptive capital system, in which economic power indefinitely suspends the normality of national and international legal orders and the capital approves the main political decisions. Thus, from the analysis of Rojava and its (des)institutions, we intended to demonstrate that a radically democratic political experience denies the exceptive capital and state system that sustains it to the extent that it acts by instituting an an-archic and a-nomic political experiment.